Dark city - Wilson, F. Paul (Francis Paul) (Wilson, F. Paul (Francis Paul). Repairman Jack novels., 2013)
"It's February 1992. Desert Storm is raging in Iraq but twenty-two-year-old Jack has more pressing matters at home. His favorite bar, The Spot, is about to be sold out from under Julio, Jack's friend. Jack has been something of a tag-along to this point, but now he takes the reins and demonstrates his innate talent for seeing biters get bit. With a body count even higher than in Cold City, this second novel of the Early Years Trilogy hurtles Jack into the final volume in which all scores will be settled, all debts paid"--